Pathology of Kaposi's sarcoma-associated herpesvirus infection - Fukumoto, Hitomi; Kanno, Takayuki; Hasegawa, Hideki; Katano, Harutaka (Frontiers in Microbiology, 2011)
Kaposi’s sarcoma-associated herpesvirus (KSHV, human herpesvirus 8, HHV-8) is a human herpesvirus, classified as a gamma-herpesvirus. KSHV is detected in Kaposi’s sarcoma (KS), primary effusion lymphoma (PEL), and some cases of multicentric Castleman’s disease (MCD). Similar to other herpes viruses, there are two phases of infection, latent and lytic. In KSHV-associated malignancies such as KS and PEL, KSHV latently infects almost all tumor cells. Quantitative PCR analysis revealed that each tumor cell contains one copy of KSHV in KS lesions. The oncogenesis by KSHV has remained unclear. Latency-associated nuclear antigen (LANA)-1 plays an important role in the pathogenesis of KSHV-associated malignancies through inhibition of apoptosis and maintenance of latency. Because all KSHV-infected cells express LANA-1, LANA-1 immunohistochemistry is a useful tool for diagnosis of KSHV infection. KSHV encodes some homologs of cellular proteins including cell-cycle regulators, cytokines and chemokines, such as cyclin D, G-protein coupled protein, interleukin-6, and macrophage inflammatory protein-1 and -2. These viral proteins mimic or disrupt host cytokine signals, resulting in microenvironments amenable to tumor growth. Lytic infection is frequently seen in MCD tissues, suggesting a different pathogenesis from KS and lymphoma.